Outcomes of subfascial endoscopic perforator ligation surgery versus open subfascial ligation surgery of incompetent perforator veins in the treatment of varicose veins - Teja, Bathala Udayee; Akhila, Bommareddy; V., Mahesh; Reddy, Ramesh; Bathala, Bhanoo Tej; Bathala, Rav Tej (International Surgery Journal, 2020)
Background: Varicose veins are common and are present in at least 10% of the general population. There are several techniques available in surgeon’s armamentarium for varicose veins treatment such as, ultrasound guided foam sclerotherapy, endovenous laser ablation, radiofrequency ablation, open perforator ligation, endoscopic perforator ligation. Methods: It was prospective randomized study. Test group underwent subfascial endoscopic perforator surgery (SEPS) by the two-port method. Control group underwent open subfascial ligation of perforators. Results: Study included 25 patients in each group. Perforator incompetence was seen in bilateral limbs in 8% in both the groups. Post op stay in open group is 7.3±0.6 days and 5.2±0.9 days in SEPS group. Post-operative day 7 VAS scoring was 1.0±0.4 in open group and 0.4±0.5 in SEPS group which is statistically significant. Post operatively wound site hematoma was seen in 9 patients in open group on post-operative day 1, which disappeared in 8 patients by day 5 and in 1 patient evacuation was done and 3 patients developed wound site hematoma in SEPS group, which resolved by day 5. Ulcer recurrence was not seen in both groups at 1 year follow up. Conclusions: This study shows the superiority of SEPS over open technique because of shorter hospital stay, lesser post-operative complications like pain, hematoma formation, wound infection, total number of perforators ligated, early recovery. Though longer follow up is needed to comment about the true superiority of SEPS versus open subfascial ligation of perforators in treatment of varicose veins.